Pengaruh Penggantian Medium terhadap Viabilitas Hepatosit Kultur 3D Organoid Hati - Sibuea, Christine Verawaty; Pawitan, Jeanne Adiwinata; Antarianto, Radiana (Nommensen Journal of Medicine, 2022)
Background : Liver organoids can be used as materials for Bioartificial Liver, to study the mechanism of liver disease and as drug test toxicity. Reconstruction of liver organoids requires optimal culture methods, culture medium and cellular components to construct liver organoids that resemble liver microstructure in vivo with optimal function. 3D culture method using hepatocytes and stem cells with PRP supplemented William's E can reconstruct liver organoids with liver function. Medium exchange is an usual method to maintain the required nutrients and to eliminate waste products, but it requires a sufficient supply of medium and supplementation. Method and the use of effective and efficient medium with optimal hepatocyte viability are urgently needed in the reconstruction of liver organoids. Objective : This study was aimed to compare the viability of primary hepatocytes in culture medium exchange liver organoids and monoculture and without culture medium exchange. Methods : Primary hepatocytes isolated from Sprague Dawley-Rats mice (250gr, n=3) were co-cultured with umbilical cord mesenchymal stem cells, cord blood CD34+ stem cells and LX2 in PRP-supplemented William's E for 14 days. The culture medium was exchanged at 48 hours, day 7 and day 14 and no culture medium exchanged in the control group. Hepatocyte viability was analyzed using the Trypan Blue Exclusion Test at 48 hours, day 7 and day 14. Results : Hepatocyte viability in culture medium exchange liver organoids was higher than without culture medium exchange, especially in monoculture, but there was no significant difference (p value> 0.05). Conclusion: Hepatocyte viability in culture medium exchange liver organoids was not significantly different from no culture medium exchange liver organoids. Culture medium exchange in monoculture supported hepatocyte viability up to day 14. Keywords: hepatocytes, liver organoids, viability, culture medium ABSTRAK Latar belakang : Organoid hati dapat digunakan sebagai bahan Bioartificial Liver, mempelajari mekanisme penyakit hati dan uji toksisitas obat. Rekonstruksi organoid hati membutuhkan metode kultur, medium kultur dan komponen seluler yang optimal untuk menghasilkan organoid hati yang menyerupai mikrostruktur hati in vivo dengan fungsi yang optimal. Metode kultur 3D menggunakan hepatosit dan sel punca mesenkimal dengan William’s E yang disuplementasi PRP dapat merekonstruksi organoid hati dengan fungsi hati. Pergantian medium merupakan metode yang sering dilakukan untuk mempertahankan nutrisi yang dibutuhkan dan untuk membuang sisa metabolit sel, tetapi membutuhkan persediaan medium dan suplementasi yang cukup banyak. Metode dan penggunaan medium yang efektif dan efisien dengan viabilitas hepatosit yang optimal sangat dibutuhkan dalam rekonstruksi organoid hati. Tujuan : Penelitian ini bertujuan untuk mengetahui perbandingan viabilitas hepatosit primer pada organoid hati dengan pergantian medium kultur dan tanpa pergantian medium kultur. Metode : Hepatosit primer yang diisolasi dari tikus Sprague Dawley-Rats (250gr, n=3) diko-kultur dengan sel punca mesenkimal asal tali pusat, sel punca CD34+ asal darah tali pusat dan LX2 dalam William’s E yang disuplementasi PRP selama 14 hari. Medium kultur diganti pada 48 jam, hari ke-7 dan hari ke-14 dan tidak dilakukan pergantian medium pada kelompok kontrol. Viabilitas hepatosit dianalisa dengan menggunakan Trypan Blue Exclusion Test pada 48 jam, hari ke-7 dan hari ke-14. Hasil : Viabilitas hepatosit pada organoid hati dengan pergantian medium kultur tampak lebih banyak dibandingkan tanpa pergantian medium kultur khususnya pada monokultur, tetapi tidak terdapat perbedaan yang signifikan (nilai p>0,05). Kesimpulan : Viabilitas hepatosit pada organoid hati dengan pergantian medium kultur tidak berbeda secara signifikan dengan organoid hati tanpa pergantian medium kultur. Pergantian medium kultur pada monokultur mendukung viabilitas hepatosit hingga hari ke-14. Kata Kunci : Hepatosit, organoid hati, viabilitas, medium kultur